12Н-quinoxaline[2, 3-b]phenoxazines: Synthesis, optical, electrochemical properties and insight into photovoltaic application. (January 2022) - Ivakhnenko, Eugeny P.; Knyazev, Pavel A.; Omelichkin, Nikolay I.; Makarova, Nadezhda I.; Starikov, Andrey G.; Aleksandrov, Alexey E.; Ezhov, Artem V.; Tameev, Alexey R.; Demidov, Oleg P.; Minkin, Vladimir I.
Abstract: A series of N-aryl derivatives of heteropentacyclic 12 Н -quinoxaline[2, 3- b ]phenoxazine (QOPO) system were synthesized and spectral, luminescent, electrochemical and optoelectronic properties of the prepared compounds studied. The compounds are well soluble in nonpolar and polar solvents, absorb in the strongest emissive part of the solar spectrum and exhibit sufficiently high photostability at air conditions. The HOMO, LUMO energy levels of the obtained QOPOs were calculated by the DFT B3LYP/6–311++G(d, p) method and assessed using the electrochemical methodology. The double-layered p-n heterojunction organic solar cells constructed on the basis of QOPOs as electron donor components, bathocuproine as the exciton blocking layer and fullerene C60 as electron acceptor displayed promising values of photovoltaic (open circuit voltage and short-circuit current density) parameters. Graphical abstract: Image 1 Highlights: New heteropentacyclic 12 Н -quinoxaline[2, 3- b ]phenoxazines (QOPO) were synthesized. Spectral, electrochemical and optoelectronic properties of the QOPOs suit to the requirements of DSSCs. QOPOs were tested as electron donors in p-n heterojunction OSC. Specimen ITO/QOPO/BTC/C60/Al OSC device showed PCE higher than 2.4%.